Positive surgical margin during radical prostatectomy: overview of sampling methods for frozen sections and techniques for the secondary resection of the neurovascular bundles. (27th February 2020) - Sighinolfi, Maria Chiara; Eissa, Ahmed; Spandri, Valentina; Puliatti, Stefano; Micali, Salvatore; Reggiani Bonetti, Luca; Bertoni, Laura; Bianchi, Giampaolo; Rocco, Bernardo
Abstract : Objective: The aim of the paper is to provide an overview of intraoperative sampling methods for frozen section (FS) analysis and of surgical techniques for a secondary neurovascular bundle (NVB) resection, as the method of surgical margin (SM) sampling and the management of a positive SM (PSM) at the nerve‐sparing (NS) area are under evaluated issues. FS analysis during radical prostatectomy (RP) can help to tailor the plane of dissection based on cancer extension and thus extend the indications for NS surgery. Evidence Acquisition: We performed a PubMed/Medical Literature Analysis and Retrieval System Online (MEDLINE), Web of Science, Cochrane Library, and Elton B. Stephens Co. (EBSCO)host search to include articles published in the last decade, evaluating FS analysis in the NS area and surgical attempts to convert a PSM to a negative status. Evidence Synthesis: Overall, 19 papers met our inclusion criteria. The ways to collect samples for FS analysis included: systematic (analysing the whole posterolateral aspect of the prostate specimen, i.e., neurovascular structure‐adjacent frozen‐section examination [NeuroSAFE]); magnetic resonance imaging (MRI)‐guided (biopsies from MRI‐suspicious areas, retrieved by the surgeon in a cognitive way); and random biopsies from the soft periprostatic tissues. Techniques to address a PSM in the NS area included: full resection of the spared NVB, from its caudal to cranial aspect, often including the rectolateral part of the Denonvilliers' fascia; partial resection of the NVB, in cases where sampling attempts to localise a PSM; incremental approach, meaning a partial or full resection that extends until no prostate tissue is found in the soft periprostatic environment. Conclusions: There is no homogeneity in prostate sampling for FS analysis, although most recent evidence is moving toward a systematic sampling of the entire NS area. The management of a PSM is variable and can be affected by the sampling strategy (difficult localisation of the persisting tumour at the NVB). The difficult identification of the exact soft tissue location contiguous to a PSM could be considered as the critical point of FS analysis and of spared‐NVB management.